Proportion of patients in south London with first-episode psychosis attributable to use of high potency cannabis: a case-control study. (March 2015) - Di Forti, Marta; Marconi, Arianna; Carra, Elena; Fraietta, Sara; Trotta, Antonella; Bonomo, Matteo; Bianconi, Francesca; Gardner-Sood, Poonam; O'Connor, Jennifer; Russo, Manuela; Stilo, Simona A; Marques, Tiago Reis; et al.
Summary: Background: The risk of individuals having adverse effects from drug use (eg, alcohol) generally depends on the frequency of use and potency of the drug used. We aimed to investigate how frequent use of skunk-like (high-potency) cannabis in south London affected the association between cannabis and psychotic disorders. Methods: We applied adjusted logistic regression models to data from patients aged 18–65 years presenting to South London and Maudsley NHS Foundation Trust with first-episode psychosis and population controls recruited from the same area of south London (UK) to estimate the effect of the frequency of use, and type of cannabis used on the risk of psychotic disorders. We then calculated the proportion of new cases of psychosis attributable to different types of cannabis use in south London. Findings: Between May 1, 2005, and May 31, 2011, we obtained data from 410 patients with first-episode psychosis and 370 population controls. The risk of individuals having a psychotic disorder showed a roughly three-times increase in users of skunk-like cannabis compared with those who never used cannabis (adjusted odds ratio [OR] 2·92, 95% CI 1·52–3·45, p=0·001). Use of skunk-like cannabis every day conferred the highest risk of psychotic disorders compared with no use of cannabis (adjusted OR 5·4, 95% CI 2·81–11·31, p=0·002). The population attributable fraction of first-episode psychosis for skunk use for our geographical area was 24% (95% CI 17–31), possibly because of the high prevalence of use of high-potency cannabis (218 [53%] of 410 patients) in our study. Interpretation: The ready availability of high potency cannabis in south London might have resulted in a greater proportion of first onset psychosis cases being attributed to cannabis use than in previous studies. Funding: UK National Institute of Health Research (NIHR) Specialist Biomedical Research Centre for Mental Health, SLaM and the Institute of Psychiatry at King's College London, Psychiatry Research Trust, Maudsley Charity Research Fund, and th European Community's Seventh Framework Program grant (agreement No. HEALTH-F2-2009-241909 [Project EU-GEI]).